Treatment of double-refractory multiple myeloma - S. V. Semochkin (Онкогематология)
In most publications on relapsed and refractory multiple myeloma, the term double-refractory refers to the loss of response to lenalidomide and proteasome inhibitors. The prognosis in the case of double-refractory multiple myeloma is poor. Usually, these are severely pretreated patients who have accumulated drug toxicity after 2 or more lines of therapy, with limited reserves of bone marrow hematopoiesis and often decompensated comorbidities. A partial solution to the problem was to use certain new drugs that have demonstrated activity as monotherapy or in combination with dexamethasone in this group of patients. This review is aimed to provide a critical review of recent clinical studies addressing this issue. According to the recent European Hematology Association and European Society for Medical Oncology (EHA-ESMO) 2021 guidelines for the diagnosis and treatment of double-refractory multiple myeloma, triple combinations should be considered, including monoclonal antibodies (elotuzumab (Elo), isatuximab (Isa), daratumumab (Dara)), dexamethasone and pomalidomide (Elo-Pd, Isa-Pd, Dara-Pd) or carfilzomib (Isa-Kd, Dara-Kd). In Russia, as of March 2021, the first two regimens were approved (Elo-Pd, Isa-Pd). Elotuzumab was tested in combination with pomalidomide in the randomized phase II ELOQUENT-3 trial (Elo-Pd vs. Pd; n = 177). Median progression-free survival was 10.3 months on Elo-Pd vs. 4.7 months on Pd (hazard ratio 0.54; 95 % confidence interval 0.34–0.86; р = 0.008). Elo-Pd superiority was observed in all subgroups, including patients with double-refractory MM, high-risk cytogenetic aberrations del17p, t(4;14), t(14;16), and increased serum LDH. The Isa-Pd triplet was approved in the randomized phase III ICARIA-MM study (Isa-Pd vs. Pd; n = 307). The median progression-free survival in this protocol was 11.5 months in the Isa-Pd group vs. 6.5 months in the Pd group (hazard ratio 0.596; 95 % confidence interval 0.44–0.81; р = 0.001). Isa-Pd triplet superiority was demonstrated in all unfavorable prognostic subgroups, including lenalidomide-refractory patients, patients with high-risk cytogenetics, and doublerefractory patients. New triplets with monoclonal antibodies represent an important option for the treatment of doublerefractory multiple myeloma.